TINJAUAN YURIDIS TERHADAP PERAN DPRD KOTA SAMARINDA DALAM PENGAWASAN TERHADAP ANGGARAN PENDAPATAN BELANJA DAERAH BERDASARKAN UNDANG – UNDANG NO. 9 TAHUN 2015 TENTANG PEMERINTAHAN DAERAH - RISKA NANDA PUSPITADEWI (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
ABSTRACT             This study entitled "Juridical Review of the Role of Samarinda City DPRD in Supervision of Regional Expenditure Revenues Based on Law Number 9 of 2015 concerning Regional Government", under the guidance of whom I respect Mrs. Kunti Widayati, SH, M.Hum as Supervisor 1 and Mrs. Fatimah Asyari, SH, M.Hum as Supervisor II.The purpose of this research is to know clearly about the mechanism of implementation and supervision of the Samarinda City Regional Expenditure Budget and aims to find out the obstacles that arise in the implementation and supervision of the Samarinda City Regional Expenditure Budget and its settlement efforts.This research is a kind of empirical normative research. Research location in Samarinda City DPRD. The type of data used is primary data to obtain library materials and regulations relating to the thesis title. Data collection techniques used are done with a literature study. Data analysis used is qualitative analysis, where the collected data will be analyzed through three stages, namely reducing data, presenting data, and drawing conclusions.From the results of the study, it can be concluded that the mechanism for the implementation of supervision of the Regional Expenditure Budget is regulated in the Law of the Republic of Indonesia Number 9 of 2015 concerning the Regional Government. The implementation and supervision mechanism for the Samarinda City Regional Expenditure Budget includes Planning, Implementation (Management), Control (Audit of Regional Financial Reports), Administration, Accounting, Reporting, and Accountability.Keywords: The Role of DPRD of Samarinda City, Mechanism of Implementation and Supervision on Local Budget of Samarinda City Revenue